Radio: An Overview of Mass Communication Media and Its Effect on World Society the 20th Century - Angga Priatna (2022)
If we talk about radio, our minds are probably will be focused on audio-based electronic media that plays favorite music or hot news was happening today. Whether we realize or not, these broadcasts maybe can we take to talk with family or friends. Such as high price of cooking oil, or information about price of pertalite. Our chats in the cheap coffee shops untill to expensive coffee shops maybe it could be the cause of student demonstrations, or the formed communities because they have a common goal. That is radio, although nowadays it has been replaced by vlogs, tiktok, or podcasts on youtube, but at least we feel its existence, even at environmental security posts or in vehicles playing audio tapes.